IN HUMAN RESOURCE MANAGEMENT, EMPLOYMENT PROVISION IS AN IMPORTANT FACTOR OF SOCIAL DEVELOPMENT (World Bulletin of Management and Law, 2022)
This article analyzes the peculiarities of the labor market of our country in providing employment, classifies the problems associated with the employment of the able-bodied population, especially young people, and develops scientific and practical proposals to increase the employment of the unemployed population
Keywords: GDP; budget; efficiency; credit